Seasonal dynamics of PM2.5 composition and optical properties in the middle Indo-Gangetic Plain: Role of secondary processing and aerosol liquid water content - Aman Deep Gupta; Seema Prajapati; Tarun Gupta (Atmospheric Environment, 2026)

Machine learning estimation of aerosol size distributions from meteorological data in the Western Himalayas - Alok Sagar Gautam; Aman Deep Vishwkarma; Karan Singh; Sanjeev Kumar; Yasti Panchbhaiya; Sneha Gautam; Chang-Hoi Ho; Yong-Sang Choi (Theoretical and Applied Climatology, 2026)

Molecular evidence of fatal theileriosis in pastoralic Gaddi breed goats in Himachal Pradesh, North India: cladistics and population structure analysis - Aman D. Moudgil; Deep Thakur; Anil K. Nehra (Tropical Animal Health and Production, 2025)

Use of Different Organic Sources of Nutrients and Azotobacter for Enhancing Fruit Quality and Yield of Dragon Fruit - Sumit Bura; Amit Jasrotia; Arti Sharma; Deep Ji Bhat; Gurdev Chand; Anil Bhat; Ranbir Singh; Deepak Khatri; Aman (Applied Fruit Science, 2025)

Improved performance of Andrographis paniculata in litchi-based agroforestry systems - Aseem Khan; Yamini Sharma; Prem Prakash Sharma; Aman Deep Ranga; Ankita Bhatia; Devansh Dogra; Atul Gupta (Agroforestry Systems, 2025)

Varying Responses to Heat Stress and Salinization Between Benthic and Pelagic Riverine Microbial Communities - Lisa Boden; Dana Bludau; Guido Sieber; Aman Deep; Daria Baikova; Gwendoline M. David; Una Hadžiomerović; Tom L. Stach; Dominik Buchner; Jens Boenigk (Environmental Microbiology, 2025)
Microbial communities play a crucial role in the functioning of freshwater ecosystems but are continuously threatened by climate change and anthropogenic activities. Elevated temperatures and salinisation are particularly challenging for freshwater habitats, but little is known about how microbial communities respond to the simultaneous exposure to these stressors. Here, we use mesocosm experiments and amplicon sequencing data to investigate the responses of pelagic and benthic microbial communities to temperature and salinity increases, both individually and in combination. Our results highlight the varying responses of freshwater microbial communities, with sediment communities exhibiting greater stability in response to environmental changes compared to water column communities, and salinisation having a more pronounced impact on microeukaryotes compared to prokaryotes. Simultaneous exposure to elevated temperature and salinity reduced the impact of salinisation on prokaryotes, while microeukaryotes were similarly affected by the combined treatments and salinisation alone. These findings emphasise the complexity of microbial responses to single and multiple stressors, underscoring the need to consider both individual and interactive effects when predicting ecosystem responses to environmental changes.

Recent progress in synthetic strategies for novel β-lactams linked with five-membered heterocycles (N/O/S): advances in medicinal chemistry (2020–2025) - Ankita Garg; Dolar Dureja; Raaina Pasricha; Pawan Deep Kaur Saini; Aman Bhalla (Medicinal Chemistry Research, 2025)

Influence of ambient particulate matter and environmental factors on the seasonal bioaerosol load in the middle Indo-Gangetic Plain - Aman Deep Gupta; Vivek Srivastava; Neha Yadav; Santosh K. Misra; Tarun Gupta (Atmospheric Environment, 2025)

Inheritance studies for pigmentation in pods of okra (Abelmoschus esculentus L. Moench) - Aman Deep Ranga; Amit Vikram; Ramesh Kumar; Rajesh K Dogra; Rajnish Sharma; Bonde Kuldeep Jagannath; Amisha Rani (Euphytica, 2024)

Assessing the response of an urban stream ecosystem to salinization under different flow regimes - Iris Madge Pimentel; Daria Baikova; Dominik Buchner; Andrea Burfeid Castellanos; Gwendoline M. David; Aman Deep; Annemie Doliwa; Una Hadžiomerović; Ntambwe A. Serge Mayombo; Sebastian Prati; Marzena Agata Spyra; Anna-Maria Vermiert; et al. (Science of The Total Environment, 2024)

A review on potential approach for in silico toxicity analysis of respirable fraction of ambient particulate matter - Aman Deep Gupta; Tarun Gupta (Environmental Monitoring and Assessment, 2023)

The Asymmetric Response Concept explains ecological consequences of multiple stressor exposure and release - Matthijs Vos; Daniel Hering; Mark O. Gessner; Florian Leese; Ralf B. Schäfer; Ralph Tollrian; Jens Boenigk; Peter Haase; Rainer Meckenstock; Daria Baikova; Helena Bayat; Arne Beermann; et al. (Science of The Total Environment, 2023)

Genotype × environment interaction for fruit yield in Okra (Abelmoschus esculentus L.) - Aman Deep Ranga; Mayur S. Darvhankar (Vegetos, 2022)

Seasonal bioaerosol load and statistical analysis within different microenvironments of an academic institute situated in the Indo-Gangetic Plain - Aman Deep Gupta; Vivek Srivastava; Tarun Gupta (Aerobiologia, 2021)

Studies on development of pumpkin based antioxidant rich table wine - Somesh Sharma; Aman Deep Thakur; Pankaj Kumar Chauhan; Rupak Nagraik; Avinash Sharma; Dinesh Kumar; Nitika Thakur (Vegetos, 2021)

Synergistic action of indole acetic acid with homobrassinolide in easing the NaCl-induced toxicity in Solanum melongena L. seedlings - Aman Deep Raju; Parul Parihar; Rachana Singh; Jitendra Kumar; Sheo Mohan Prasad (Acta Physiologiae Plantarum, 2020)